Description of gender, intravenous drug administration, and QT interval view at dr. Wahidin general hospital sudirohusodo Makassar - Suradi Efendi; Nour Sriyanah; Ayu Sri Wahyuni; Nurnainah Nurnainah; Fitriani Fitriani; Nur Wahyuni Arif (Universitas Aisyah Pringsewu, 2023)
The QT interval is a picture of the activity of the heart's ventricles, starting from depolarization to ventricular repolarization which can be influenced by several factors, namely drugs, gender, inflammatory conditions, obesity, heart failure, and others. Basic Health Research Data in 2018, states that in Indonesia there are around 2,784,064 individuals who suffer from heart disease and every year this number will continue to increase. The purpose of this study was to find out whether there was a relationship between sex and intravenous administration of drugs with QT prolongation. This research is a type of descriptive research. With a total sample of 118 respondents, it was carried out by observing medical records. The results of statistical tests on the sex variable with QT prolongation showed p = 0.007, and on the intravenous drug administration variable with QT prolongation showed p = 0.002. The conclusion of this study was that there was a relationship between gender and intravenous drug administration with QT prolongation. It is necessary to pay attention to the side effects of drug administration given to patients. And for future researchers, it is hoped that this study can become a reference by using other variables related to QT interval prolongation such as drug side effects and conditions of electrolyte disturbances. Abstrak: Interval QT merupakan gambaran aktivitas ventrikel jantung, dimulai dari depolarisasi hingga repolarisasi ventrikel yang dapat dipengaruhi oleh beberapa faktor yaitu obat-obatan, jenis kelamin, kondisi inflamasi, obesitas, gagal jantung, dan lainnya. Data Riset Kesehatan Dasar pada tahun 2018, menyatakan di Indonesia terdapat sekitar 2.784.064 individu yang menderita penyakit jantung dan setiap tahunnya angka tersebut akan terus meningkat. Tujuan penelitian ini mencari tahu adakah hubungan jenis kelamin dan pemberian obat melalui intravena dengan pemanjangan interval QT. Penelitian ini merupakan jenis penelitian deskriptif. Dengan jumlah sampel sebanyak 118 responden yang dilakukan dengan cara observasi rekam medik. Hasil uji statistik pada variabel jenis kelamin dengan pemanjangan interval QT menunjukkan p=0,007, dan pada variabel pemberian obat melalui intravena dengan pemanjangan interval QT menunjukkan p=0,002. Simpulan penelitian ini terdapat hubungan antara jenis kelamin dan pemberian obat melalui intravena dengan pemanjangan interval QT. Perlu diberikan perhatian terhadap efek samping dari pemberian obat yang diberikan kepada pasien. Dan untuk peneliti berikutnya diharapkan studi ini dapat menjadi acuan dengan menggunakan variabel lain terkait pemanjangan interval QT seperti efek samping obat dan kondisi gangguan keseimbangan elektrolit.